SPEAK UP YOUR STUDENTS WITH MIRROR, HANDS AND EYES - Nur Effendi (Universitas PGRI Madiun, 2015)
Mirror, Hands and Eyes is a technique to teach speaking which use mimic in it. This research has purposes to describe how the implementation of Mirror, Hands and Eyes, and to know the advantages and disadvantages of the implementation of Mirror, Hands and Eyes in teaching speaking. This is descriptive qualitative research. The researcher takes three sources of the data, social situation, informant, and document. The sample is using purposive sampling. Observation, interview and documentation are the technique used by the researcher to collect the data. Theoretical and methodological triangulation used by the researcher to measure the valid data. The techniques of analyzing data are compiling, disassembling, reassembling, interpreting, and concluding.The advantages of this technique are increase the students’ speaking skill, increase the students’ enthusiast, easily follow the correct pronunciation, lock the students’ focus. The disadvantages are the technique disallow the students build new words, and the lack of vocabulary makes the students face the difficulties to make sentences. It can be concluded by the theory of Panesso and Brown with little modification to make students speak up that show the implementation of Mirror, Hands and Eyes works in chronological ways with pre-activity, whilst activity, and post activity inside.